Philosophical Foundations of Paulo Freire's Critical Pedagogy - Moreira Cedeño, Steeven Andrés (2023)
To say a true word is to change the world" Paulo Freire, who was an educator, politician and philosopher who lit the fuse of an educational revolution that is present to this day. In this short article, you will find reflections that are linked to the thought of Paulo Freire and its foundations from the philosophy of education. The history and experiences that Freire lived will be exposed, and how they were a trigger for the creation of an innovative proposal, critical pedagogy, which I carry out from the observation and reflection of the social actors of the date. This concept of critical pedagogy will be addressed through a review of ideologies, philosophical currents and authors who debated, complemented and consolidated the work of Paulo Freire. The main foundations of the philosophy of education will be presented together with the three main thoughts of Paulo Freire, the conception of the oppressed and oppressor, referencing an analogy between the educational system and the state; dehumanization and literacy, , investigating the actions of the oppressed and oppressor that lead to the dehumanization of man and how Freire proposes the method of literacy to overcome it; banking education versus liberating education, looking for concepts and theoretical references that explain these concepts.  Finally, it will conclude with a reflection and critique of the educational reality that is currently being lived.